The Production of Testosterone and Gene Expression in Neonatal Testes of Rats Exposed to Diisoheptyl Phthalate During Pregnancy is Inhibited - Ji, Bin; Wen, Zina; Ni, Chaobo; Zhu, Qiqi; Wang, Yiyan; Li, Xiaoheng; Zhong, Ying; Ge, Ren-Shan (Frontiers in Pharmacology, 2021)
Background: Diisoheptyl phthalate (DIHP) is a phthalate plasticizer and belongs to the branched-chain phthalate. Here, we reported the effects of gestational exposure to DIHP on testis development in male rats. Methods: Pregnant Sprague-Dawley rats were orally fed with vehicle (corn oil, control) or DIHP (10, 100, 500, and 1000 mg/kg) from gestational day (GD) 12 to 21. At GD21, serum testosterone levels, fetal Leydig cell number and distribution, and testicular mRNA and protein levels, the incidence of multinucleated gonocytes, and focal testicular hypoplasia in the neonatal testis were measured. Results: DIHP increased fetal Leydig cell cluster size and decreased fetal Leydig cell size with LOAEL of 10 mg/kg. DIHP did not affect fetal Leydig cell number. DIHP significantly lowered serum testosterone levels, down-regulated the expression of steroidogenesis-related genes (Lhcgr, Star, Cyp11a1, Hsd3b1, Cyp17a1, and Hsd17b3) and testis descent-related gene (Insl3) as well as protein levels of cholesterol side-chain cleavage enzyme (CYP11A1) and insulin-like 3 (INSL3). DIHP dose-dependently increased the percentage of multinucleated gonocytes with the low observed adverse-effect level (LOAEL) of 100 mg/kg. DIHP induced focal testicular hypoplasia. Conclusion: Gestational exposure to DIHP causes testis dysgenesis in rats.